The Effect of Different Therapeutic Modalities on Demodex Densities and Clinical Symptoms of Patients with Demodicosis - Yalıcı Armağan, Başak; Atakan, Nilgün (Acta Medica, 2022)
Background: Demodicosis represents cutaneous diseases caused by cutaneous overpopulation of Demodex mites. The aim of this study was to evaluate the effect of different treatment options on Demodex densities (Dds) and clinical symptoms of patients with demodicosis. Methods: Patients with high Dds in two consecutive standardized skin surface biopsies (SSSB1>5 D/cm2 or SSSB2>10 D/cm²) and concomitant clinical symptoms were evaluated retrospectively. Measurements of treatment effectiveness included clinical improvement and normalization or reducing of Dds. Results: A total of 21 patients included in the study. Five patients received topical permethrin and crotamiton whereas 16 patients received systemic metronidazole in combination with topical permethrin and/or crotamiton. The treatment was continued with topical ivermectin in 2 patients who had failure with other treatments. The median treatment duration was 3 months (IQR 1-4). Pre- and post-treatment median Dds decreased 30 to 14 D/cm2 on SSSB1 whereas 81 to 80 D/cm2 on SSSB2, respectively. There was no statistically significant decrease in Dds on SSSB1 and SSSB2 after the treatment (p=0.173 and p=0.134, respectively). Clinical improvement was recorded in a total of 14 patients (66.6%) of whom only 2 patients (9.5%) had normalization on Dds. Additionally, topical ivermectin provided a rapid clinical improvement and normalization on Dds in both 2 patients. Conclusion: Irrespective of the treatment, more than two-thirds of the patients improved clinically without a significant change in Dds. This finding may suggest that the treatment response has been mostly associated with the anti-inflammatory properties of the agents. Topical ivermectin seems to be a more suitable treatment option for demodicosis with positive effects on both clinical findings and Dds.